2022
DOI: 10.3390/ijms23158652
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Toxicity Is Regulated by Peroxisome Proliferator-Activated Receptor δ in Human Proximal Tubular Cells

Abstract: Cadmium (Cd) is a toxic heavy metal that is widely present in the environment. Renal proximal tubule disorder is the main symptom of Cd chronic poisoning. Our previous study demonstrated that Cd inhibits the total activities of peroxisome proliferator-activated receptor (PPAR) transcription factors in human and rat proximal tubular cells. In this study, we investigated the involvement of PPAR in Cd renal toxicity using the HK-2 human proximal tubular cell line. Among PPAR isoform genes, only PPARD knockdown si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…47 As heavy metals are generally toxic, their accumulation may cause acute or chronic oxidative stress, lead to excessive ROS production. 48 By covering CdS/ZnS nanoparticles with the PEGylated cRGD liganddecorated CCM, targeted delivery of nanoparticles to glioblastoma was achieved. Therefore, accumulation of CdS/ ZnS nanoparticles in glioblastoma would result in better treatment efficacy and reduced side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 As heavy metals are generally toxic, their accumulation may cause acute or chronic oxidative stress, lead to excessive ROS production. 48 By covering CdS/ZnS nanoparticles with the PEGylated cRGD liganddecorated CCM, targeted delivery of nanoparticles to glioblastoma was achieved. Therefore, accumulation of CdS/ ZnS nanoparticles in glioblastoma would result in better treatment efficacy and reduced side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium is a kind of heavy metal . As heavy metals are generally toxic, their accumulation may cause acute or chronic oxidative stress, lead to excessive ROS production . By covering CdS/ZnS nanoparticles with the PEGylated cRGD ligand-decorated CCM, targeted delivery of nanoparticles to glioblastoma was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the mechanisms underlying Cd-induced reproductive toxicity are complex [ 16 , 17 , 18 , 19 ]. The presence of Cd significantly increases the expression of blood vessel-related proteins, including CD31, NG2, αSMA, and caveolin-1, which stimulate abnormal proliferation of vascular endothelial cells and result in high blood pressure and vascular damage [ 20 ].…”
Section: Introductionmentioning
confidence: 99%